Molecular characterization and evaluation of potential isolated bacteria in optimizing former coal mining land as a planting media in East Kalimantan, Indonesia - YUNI SRI RAHAYU; YULIANI YULIANI; MAHANANI TRI ASRI; DWI ANGGOROWATI RAHAYU (Society for Indonesian Biodiversity, 2024)
Abstract. Rahayu YS, Yuliani, Asri MT, Rahayu DA. 2024. Molecular characterization and evaluation of potential isolated bacteria in optimizing former coal mining land as a planting media in East Kalimantan, Indonesia. Biodiversitas 25: 4059-4066. East Kalimantan is an extensive province in Indonesia dedicated to coal mining activities. Despite the potential, several coal mining enterprises do not implement land reclamation procedures before abandoning the mines. This situation often leads to low soil fertility and challenges in effectively converting the resulting marginal land into productive terrain. Several reports have shown the importance of concerted efforts to address those challenges. Therefore, this study aims to isolate, characterize, and evaluate endophytic microorganisms in optimizing former coal mining areas using the partial sequence of 16S rRNA. The construction of the phylogenetic tree topology between samples and the close relatives from GenBank was analyzed using the Neighbor-Joining (NJ) and Maximum-Likelihood (ML) methods with the Kimura 2-Parameter (K2P) calculation model (with 1,000 bootstraps). The resulting cladogram could be divided into two major clusters, with cluster 1 comprising two distinct clades, namely the Bacillus genus clade and clade 2 consisting of the Genus Achromobacter and Pseudomonas. Meanwhile, cluster 2 was divided into two clades: Bacillus alvei and Bacillus pantothenticus. Each group in these clades was then further categorized based on the species, with a bootstrap value of 100%. The molecular data identification revealed five variations of nucleotide bases, and the genetic distance average value within the ingroup was 1.0%. The results revealed that species similarities existed between Pseudomonas guariconensis, Bacillus mycoides, Bacillus pantothenticus, Bacillus sphaericus, Bacillus mycoides, Achromobacter xylosoxidans, Bacillus sphaericus, Bacillus firmus, Bacillus stearothermophilus, Bacillus alvei. Based on these results, the 16S ribosomal RNA (16S rRNA) sequences had successfully differentiated bacteria in optimizing former coal mining areas in East Kalimantan.